THE INFLUENCE OF COOPERATIVE LEARNING TEAM ASSISTED INDIVIDUALIZED (TAI) TYPE TO THE STUDENTS’ LEARNING MOTIVATION AND ENGLISH READING COMPREHENSION AT STIK BINA HUSADA PALEMBANG - Agus Wahyudi (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
As an international language, English plays an important role in making people acquire knowledge, information, skills in communication in order to compete with other people in the international level. For example, those who master English can easily communicate with people from other countries in English and can read scientific books written in English. In Indonesia, there is a great demand for the people to learn English both in formal education and in non-formal education. In order to take an active part or even to survive in the present state of technological advancements and rapid growth of the globalization, someone has to have proficient mastery of the English language. One way to develop students’ achievement is through cooperative learning, they can work together, appreciate others’ opinion and give others chance to share their opinion, therefore the students can have higher motivation because they are encouraged by others. The sample of this research is STIK Bina Husada students, the researcher gives treatment to the experimental group, that is Team Assisted Individualized (TAI), the results are compared between before and after the treatment, to analyze the motivation changes, the researcher distributes a quetionnaire through likert skale and t test, and to analyze students’ reading comprehension, the researcher distributes a reading test. Based on statistical analysis, it is found that there is significant influence of cooperative learning to the students’ learning motivaion and english reading comprehension where t value in students motivaion 8.212, reading comprehension 7.008, in .000 significant level. Keywords: TAI, learning motivation, reading achievement